Mathematical prediction of nitrogen and phosphorus removal from piggery wastewater by horizontal sub-surface flow constructed wetland. - Udom, I. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Mathematical equations were derived for estimation of nitrogen and phosphorus removal from piggery wastewater in horizontal subsurface flow constructed wetlands. The model inputs included wastewater inflow, retention, plant uptake and nutrient loss to the atmosphere by volatilization of nitrogen. Plant die off, precipitation and exchange with subsurface were considered negligible. The calibration and validation of the model was carried using different sets of experimental data generated from a pilot constructed wetland monitored over a period of seven months. The results show that the amount of nitrogen and phosphorus concentrations decreased exponentially within three days of retention in the wetland and, thereafter, the reduction appeared constant over higher retention time subject to the decay coefficient. There was high correlation between the simulated and observed parameters with R2 = 0.9537 for nitrogen and 0.9912 for phosphorus respectively. The low values of the mean bias error (ME) of 0.211 and 0.139, root mean square error (RMSE) of 0.32 and 0.18, and relative error of RE of 24 and 12%, demonstrated the ability of the model to predict nutrient removal accurately. The models efficiencies of 84 and 77% and index of agreements of 0.6527 and 0.8676 for nitrogen and phosphorus respectively, indicate an acceptable level of the models predictive capacities. The linear regression coefficients appear reasonable given that the system was a natural system located in the field, where uncontrolled influencing factors could weaken optimal performance. Because of challenges associated with Scaling-up this result.  longer field studies are recommended. The models developed in this study considered the features of horizontal-subsurface-flow constructed-wetlands for removal of nitrogen and phosphorus from piggery wastewater. The high correlation between the developed models and the calibrated parameters showed that they are rational. The models can be used to simulate nitrogen and phosphorus removal in horizontal-subsurface-flow constructed-wetlands. The performance of these models meets the water quality discharge or reuse standards of Nigeria for wastewater discharge to land and surface water.